Hydrocarbons and Russian foreign policy in the post-communist era (1991-2008): A case study. - Jeffery, Jared (Department of Political Studies, 2014)
This thesis aims to analyse the effect of hydrocarbons on Russian foreign policy in the post-communist period. In doing so it employs a constructivist meta-theory (actorstructure framework) and Susan Strange's approach to international political economy (IPE). The role of hydrocarbons in both the international political economy and Russia's domestic political economy is analysed. Thereafter a historical narrative outlining the affect of hydrocarbons on foreign policy from 1991-2008 is offered. There is also a brief focus on the role of Gazprom in Russian foreign policy. It is found that hydrocarbons affected Russian foreign policy through the impact they had on the state's ability to control the domestic political economy (which was diminished in the 1991-1999 period, but strengthened as international oil prices rose thereafter). Hydrocarbons, though a source of power, are also found to tie the Russian state to the interdependent international political economy of the globalised era. The analysis finds that the case supports the constructivist emphasis on the importance of understanding domestic issues when addressing the foreign policies of states. It also finds that the approaches used, Wendt's constructivism and Strange's IPE theory, work well in conjunction to illuminate foreign policy issues. A criticism of Strange's approach, however, is highlighted. She fails to give adequate attention to matters of geography in her model. This, it is argued, would be a fruitful endeavour for future IPE analysis, especially if addressed through the case of hydrocarbons in the IPE.